Aplikasi Seni Bina Rumah Tradisional Pada Rancang Bangun Kontemporer Studi Kasus Rancangan Galeri Seni Kriya Di Siak Sri Indrapura - Tri Maelawati; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Malay people defined house just not as residence, but also as the light of life, hereditary place, anchored place of the kin, past merchants stopover and parents debt to their children. Thisresearch purpose identified characteristic and ornamen decoration traditional home building art Malay in Siak. Research methodology used through field surveys, documentation, and analysis oftraditional malay buildings such as Datuk Zein Pesisir house, Datuk Djalil house, Sharwan Hamid house, Panjang Palace, Paraduan Palace and Kerapatan Tinggi Hall. The results of this researchexplained how application traditional home building art of Siak can be applied to contemporary design by applying characteristic of Malay Siak Building like structure, column, ladder, wall, door,window, roof, and ornament of decoration. This Researh be also confirmed that traditional home building art can be an inspiration and applied to contemporary design.Keywords: Architecture, Malay, Siak